Beyond age effects in instructional L2 learning revisiting the age factor - Pfenninger, Simone E. 1980-; Singleton, David M. 1948- (Second language acquisition, 2017)
This book constitutes a holistic study of how and why late starters surpass early starters in comparable instructional settings. Combining advanced quantitative methods with individual-level qualitative data, it examines the role of age of onset in the context of the Swiss multilingual educational system and focuses on performance at the beginning and end of secondary school, thereby offering a long-term view of the teenage experience of foreign language learning. The study scrutinised factors that seem to prevent young starters from profiting from their extended learning period and investigated the mechanisms that enable late beginners to catch up with early beginners relatively quickly. Taking account of contextual factors, individual socio-affective factors and instructional factors within a single longitudinal study, the book makes a convincing case that age of onset is not only of minimal relevance for many aspects of instructed language acquisition, but that in this context, for a number of reasons, a later onset can be beneficial